SOSIALISASI DAN PELATIHAN PENANAMAN MANGROVE DI KAMPOENG KEPITING KELURAHAN TUBAN, KECAMATAN KUTA, KABUPATEN BADUNG-BALI - I Wayan Suanda; IBG Darmayasa; A.A. Ketut Darmadi; Yan Ramona (LP3M Universitas PGRI Mahadewa Indonesia, 2024)
Tuban Village, Kuta District, Badung Regency has quite a wide coastline and is the estuary of several rivers in Badung Regency. Geologically, the beach consists of alluvium deposits composed of pebbles, gravel, sand, silt and clay resulting from river water and sea water sedimentation processes, which are very good for the growth of mangroves. Mangroves are not only a collection of plants, but are one of the natural resources that can provide benefits to the human life and the lives of the marine biota. This condition did not last long due to rapid development causing the conversion of coastal land for fisheries cultivation, settlements and industry which had an adverse impact on the mangrove ecosystem. The death of mangroves and depletion of living habitat resulted in a decreasing mangrove population. The existence and sustainable of the mangrove forests need to be maintained through local community involvement in the form of Kampoeng Kepiting ecotourism to gain economic value. The mangrove forest rehabilitation program takes the form of planting and maintenance as one of the efforts to restore the mangrove ecosystem in Kampoeng Kepiting, Tuban Village, Kuta District.